Endurance training and elite young athletes - Armstrong, N.; Barker, A. R. (The Elite young athlete, 2011)
Endurance training consists of a structured exercise programme that is sustained for a sufficient length of time with sufficient intensity and frequency to induce an improvement in aerobic fitness. Elite young athletes generally have higher peak oxygen uptakes (peak VO2) than their untrained peers largely due to their greater maximal stroke volumes. Trained young athletes have faster VO2 kinetic responses to step changes in exercise intensity but whether this is due to enhanced oxygen delivery or increased oxygen utilization by the muscles remains to be explored. Blood lactate accumulation in young athletes during submaximal exercise is lower than in untrained youth and this appears to be due to enhanced oxidative function in the active muscles. No well-designed, longitudinal endurance training studies of elite young athletes have been published. Even in the general paediatric population peak VO2 is the only component of aerobic fitness on which there are sufficient data to examine dose-response effects of endurance training. The existence of a maturational threshold below which children are not trainable remains to be proven. The magnitude of training responses is independent of sex. Pre-training peak VO2 has a moderate but significant inverse relationship with post-training peak VO2 which suggests that elite young athletes are likely to experience smaller increases in peak VO2 with further endurance training than untrained youth. Empirical evidence strongly indicates that both trained and untrained young people can benefit from endurance training but the relative intensity of exercise required for optimum benefits is higher than that recommended for adults.